Perbedaan Laju Pembusukan Mencit (Mus musculus) di Air Tawar, Air Laut, dan Udara Terbuka - Sitohang, Zebby; Zaluchu, Ricka Brilianty; Nawan (Fakultas Kedokteran Universitas Palangka Raya, 2023)
Decomposition is affected by many factors that can slow down or speed up the rate of decomposition of a corpse, and medium is one of the factors. The mediums that were used for this experiment were freshwater, saltwater, and outdoor surface. These mediums have distinct qualities and quantities of decomposers. House mice (Mus musculus), as the object of this experiment, have a few certain characteristics that are relatively similar to humans. The objective is to prove whether there was a difference in the rate of decomposition between freshwater, saltwater, and outdoor surface using mice that had been euthanized beforehand. The mice for the outdoor medium were euthanized by cervical dislocation, meanwhile the mice for both aquatic mediums were euthanized by getting drowned. The average rates of decomposition of the three mediums would then be obtained and analyzed. The fastest average decomposition rate happened on the outdoor surface (±48 hours), followed by the freshwater (±60 hours) and then in the saltwater (±72 hours). The statistical test showed that there is a significant difference in the average rates of decomposition between freshwater, saltwater, and outdoor surface.